Divergent evolution of low-complexity regions in the vertebrate CPEB protein family - Vaglietti, Serena; Boggio Bozzo, Stefania; Ghirardi, Mirella; Fiumara, Ferdinando (Frontiers in Bioinformatics, 2025)
The cytoplasmic polyadenylation element-binding proteins (CPEBs) are a family of translational regulators involved in multiple biological processes, including memory-related synaptic plasticity. In vertebrates, four paralogous genes (CPEB1-4) encode proteins with phylogenetically conserved C-terminal RNA-binding domains and variable N-terminal regions (NTRs). The CPEB NTRs are characterized by low-complexity regions (LCRs), including homopolymeric amino acid repeats (AARs), and have been identified as mediators of liquid-liquid phase separation (LLPS) and prion-like aggregation. After their appearance following gene duplication, the four paralogous CPEB proteins functionally diverged in terms of activation mechanisms and modes of mRNA binding. The paralog-specific NTRs may have contributed substantially to such functional diversification but their evolutionary history remains largely unexplored. Here, we traced the evolution of vertebrate CPEBs and their LCRs/AARs focusing on primary sequence composition, complexity, repetitiveness, and their possible functional impact on LLPS propensity and prion-likeness. We initially defined these composition- and function-related quantitative parameters for the four human CPEB paralogs and then systematically analyzed their evolutionary variation across more than 500 species belonging to nine major clades of different stem age, from Chondrichthyes to Euarchontoglires, along the vertebrate lineage. We found that the four CPEB proteins display highly divergent, paralog-specific evolutionary trends in composition- and function-related parameters, primarily driven by variation in their LCRs/AARs and largely related to clade stem ages. These findings shed new light on the molecular and functional evolution of LCRs in the CPEB protein family, in both quantitative and qualitative terms, highlighting the emergence of CPEB2 as a proline-rich prion-like protein in younger vertebrate clades, including Primates.